2019
DOI: 10.2174/2211536608666181203103233
|View full text |Cite
|
Sign up to set email alerts
|

Common Variants of the Plant microRNA-168a Exhibit Differing Silencing Efficacy for Human Low-Density Lipoprotein Receptor Adaptor Protein 1 (LDLRAP1)

Abstract: Background: The discovery that a plant microRNA (miRNAs) from rice (Oryza sativa miR168a) can modify post-transcriptional expression of the mammalian. Low-Density Lipoprotein Receptor Adaptor Protein 1 (LDLRAP1) gene highlights the potential for cross-kingdom miRNAmRNA interactions. Objective: To investigate whether common variants of the conserved miR168a family have the capability for similar cross-kingdom regulatory functions, we selected sequences from three dietary plant sources: rice (Oryza sativa), t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 30 publications
0
13
0
Order By: Relevance
“…different studies demonstrated that fecal miRNAs can be derived from foods and can be absorbed by intestinal epithelia modulating the expression levels of host genes (162,163). These miRNAs are mainly planted exosome-derived miRNAs; however, several studies showed that milk-derived miRNAs play key roles (164)(165)(166).…”
Section: Possible Mechanisms Of Carcinogenesis Induced By Dysbiosismentioning
confidence: 99%
“…different studies demonstrated that fecal miRNAs can be derived from foods and can be absorbed by intestinal epithelia modulating the expression levels of host genes (162,163). These miRNAs are mainly planted exosome-derived miRNAs; however, several studies showed that milk-derived miRNAs play key roles (164)(165)(166).…”
Section: Possible Mechanisms Of Carcinogenesis Induced By Dysbiosismentioning
confidence: 99%
“…For example, mtr-miR168a was predicted to target AGO1 in plants and PVP in humans, functions associated with pathogen (namely, viruses) defence, in both approaches. The miR168a is part of a conserved family of plant miRNAs among different species, but as we seen in Supplementary Figure 2 and other cited literature (Lang et al, 2019), differences exist between dicot and monocot species. The predicted human targets observed in previously published researches (Zhang et al, 2012; Javed et al, 2017), were not found in the enriched process or sequence similarity with our approaches (see Supplementary Table 1 ).…”
Section: Discussionmentioning
confidence: 66%
“…Other genes (ST8SIA1, RGS6, IL18RAP, PVR, SYN2, PPFIA1, ZDHHC18, B3GAT1) were predicted in our network-based pipeline to be targeted by mtr-miR168 in humans ( Supplementary Table 1 ). This may be due to the fact that, even if miR168a is part of conserved miRNA family, some differences in nucleotide sequences are present among monocot and dicot species and these can alter the structural accessibility and target selection (Lang et al, 2019). When aligning the osa-miR168a with its counterpart in M. truncatula , the sequence similarity was of 80.95%, showing important mismatches in the seed region ( Supplementary Figure 2 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Some studies have found minor concentrations of pl-miR in humans and animals (Zhang et al, 2016). The inclusion of pl-miR into the recipient’s organism causes reproducible changes of some properties and physiological processes in it (Cui et al, 2017; Javed et al, 2017; Lang et al, 2019; Vaucheret et al, 2012; Zhang et al, 2012). ex-miR involvement in the regulation of recipient gene expression may affect disease (Chin, Fong & Somlo, 2016; Gopinath, 2019; Hou et al, 2018; Jones et al, 2016).…”
Section: Introductionmentioning
confidence: 99%